Social Media as a strategic tool for Corporate Communication - Gómez Vázquez, Lina Margarita; Soto Vélez, Ivette (Instituto de Investigación en Relaciones Públicas, 2011)
Companies around the globe are embracing and adapting social media for many different intentions: customer service, marketing, internal communications, public relations or corporate social responsibility, etc. It is now a reality that social media is channging the way stakeholders and companies communicate daily, providing opportunities for collaboration, participation, interactivity, and engagement. Therefore, social media is conceived today in the corporate world as a strategic communication partner, driving new and unique possibilities for organizations to engage stakeholders in conversations. We are witnesses of a new digital era where consumers are becoming active users rather than passive individuals, changing dramatically how society operates. But these useful technological tools are employed widely and precisely by corporations in order to facilitate and improve communications? This research aims to discover the usage of different social media platforms by Puerto Rican companies. A content analysis was performed to the Facebook and Twitter official profiles of the top 400 locally owned Puerto Rican companies of 2009. The principal objective was to find if social media sites were mainly used as a strategic tool for corporate communication that can enhance stakeholder participation and engagement. Results showed that Puerto Rican companies are not employing social media platforms for improving communications with different stakeholders, failing to take advantage of the enormous possibilities that social media has for communication.
Los Medios Sociales como una herramienta estratégica para la Comunicación Corporativa
Keywords: Relaciones públicas; Comunicación en la empresa; Relaciones Públicas; Comunicación Estratégica; Dirección de Comunicación